MECONIUM AND URINARY PATTERNS OF HEALTHY TERM NEWBORNS IN A TERTIARY CARE HOSPITAL OF WESTERN NEPAL- A PROSPECTIVE OBSERVATIONAL STUDY - Gupta, Badri Kumar; Kaphle, Raju; Gupta, Binod Kumar; Shresth, Sandeep; Kumar, Navneet Raj; Chaudhary, Nagendra (Journal of Universal College of Medical Sciences, 2018)
Introduction: The time of passage of the newborn’s first meconium/stool is an indicator of health and is used to screen for normal gastrointestinal tract function. Most newborns urinate after birth, and this is an indication of normal renal function. The aim of this study is to investigate the meconium/stool and urinary patterns of healthy neonates so that it will help us to know the average time of passing meconium and Urine in newborns. Materials and Methods: A hospital based observational study was conducted for a period of one year in healthy term newborns delivered at UCMS-TH, a tertiary care hospital in western Nepal. Newborns with a gestational age of ≥ 37 weeks delivered by normal vaginal delivery or cesarean section were included. The newborns were fed either breast milk exclusively or a combination of breast milk and formula. The frequency of meconium/stool and urine passage was recorded throughout their hospital stay with their timings. Babies with congenital anomalies were excluded from the study (like imperforate anus, cleft lip and palate and spina bifida, colloidal baby). Results: Out of 1050 delivered babies, 5 were excluded from final analysis as they did not meet the inclusion criteria. The study showed that majority (97.8%) of newborns passed meconium within 24 hours of life while only 2% babies passed meconium after 1st day (24 hours-48 hours) suggesting that majority of newborns pass stool within 48 hours of life. Also, the study showed that majority (99.8%) of babies passed urine within first 12 hours while only 0.2 % babies passed urine between 13-24 hours suggesting that most babies passed urine within first 12 hours. Conclusions: It was observed in study that average time of passage of meconium in most of the babies were before 48 hours and passage of urine within 12 hours. Journal of Universal College of Medical Science Vol. 6, No. 1, 2018, page: 8-10